Molecular detection and genotyping of bovine viral diarrhea virus in Selangor, Malaysia - Khalid, Nurulhidayah; Arshad, Siti Suri; Degu, Nurhusien Yimer; Ramanoon, Siti Zubaidah; Sadiq, Mohammed Babatunde (Network for the Veterinarians of Bangladesh, 2024)
Objective: Bovine viral diarrhea (BVD) disease is a viral infection in cows caused by a sin¬gle-stranded plus-sense RNA virus of the Pestivirus genus under the Flaviviridae family. The clini¬cal manifestation of BVD mainly includes diarrhea and immunosuppression, thereby exacerbating various respiratory diseases. This study was conducted to detect and molecularly characterize the bovine viral diarrhea disease virus (BVDV) in cattle on selected farms in Selangor, Malaysia. Materials and Methods: A reverse transcription polymerase chain reaction (RT-PCR) was performed for antigen detection in 253 plasma samples collected from cows using a cross-sectional study design. We selected the 5 untranslated regions (5’-UTR) region and the E2 region to compare the genetic differences between the isolates. Results: One sample was found to be positive (1/253) following RT-PCR targeting the conserved 5’-UTR region of BVDV. Thus, BVDV antigen prevalence was 0.40% (95% confidence interval: 0.0%–2.2%). By targeting the hypervariable E2 region of the isolated virus, UPM/MAL/BVDV/D17, the virus was classified under the subgenotype BVDV-1a. Conclusion: BVDV is present and circulating on selected cattle farms in Selangor, Malaysia. Given the presence of BVDV in several subgenotypes, the screening of all incoming cattle at Malaysia’s border is pertinent to prevent the entry of other BVDV subgenotypes into the country.